CHANGES IN URINARY CELLS IN EXPERIMENTAL HEATSTROKE RABBITS - Cao Hong, Phuc; Vu, Quang Phong, Do Ngoc Hop, Nguyen Thi Thu Hien (Tạp chí Sinh lý học Việt Nam, 2022)
Objective: describing the changes in urinary cells in experimental heatstroke rabbits. Methods: experimenting on the 23 rabbits, protocol: temperature 420C, humid 60%, time 2,5 hours, indexes: urinary erythrocytes, leukocytes, survival time, core temperature. Results: the rate of urinary erythrocyte rabbits increased, about 82.6% at 60 min, 65,2% at 24 hours after heatstroke meanwhile it was 0% before heatstroke (0%). The rate of urinary leukocyte rabbits was 0%. The grade of urinary erythrocyte did not relate to clinical grade, core temperature and survival time. Conclusion: there were the urinary erythrocyte but not urinary leukocyte in experimental heatstroke.